A fast and low‐cost spray method for prototyping and depositing surface‐enhanced Raman scattering arrays on microfluidic paper based device. Issue 15 (2nd August 2013) - Li, Bowei; Zhang, Wei; Chen, Lingxin; Lin, Bingcheng
<x xml:space="preserve">Abstract</x> In this study, a fast, low‐cost, and facile spray method was proposed. This method deposits highly sensitive surface‐enhanced Raman scattering (SERS) silver nanoparticles (AgNPs) on the paper‐microfluidic scheme. The procedures for substrate preparation were studied including different strategies to synthesize AgNPs and the optimization of spray cycles. In addition, the morphologies of the different kinds of paper substrates were characterized by SEM and investigated by their SERS signals. The established method was found to be favorable for obtaining good sensitivity and reproducible results. The RSDs of Raman intensity of randomly analyzing 20 spots on the same paper or different filter papers depositing AgNPs are both below 15%. The SERS enhancement factor is approximately 2 × 107. The whole fabrication is very rapid, robust, and does not require specific instruments. Furthermore, the total cost for 1000 pieces of chip is less than 20. These advantages demonstrated the potential for growing SERS applications in the area of environmental monitoring, food safety, and bioanalysis in the future.